The Use of Moving Class Learning Model to Enhance Speaking Skills Viewed from Motivation - Gusti Bagus Adri Yogha Reformana; Ni Wayan Prami Wahyudiantari; Huang Yan Wang (Journal of Language and Literature Studies, 2024)
The moving class is a teaching and learning model designed to infuse the learning environment with a fresh atmosphere. This model involves the systematic rotation of students between classrooms according to a predetermined schedule, thereby facilitating varied interactions and experiences. In this context, the present study endeavors to assess the effectiveness of the moving class learning model in enhancing students' speaking skills, with a specific focus on motivation. Employing classroom action research (CAR) as the methodological framework, the study progresses through distinct phases, including planning, implementation, evaluation, and reflection. The research participants consist of second-grade students from SMP Dwijendra Mataram, and the evaluation encompasses various aspects of speaking skills, including pronunciation, accuracy, grammar, vocabulary, and comprehension. Data collection methods include speaking tests and observation sheets to provide a comprehensive understanding of student performance. Through meticulous analysis, the study concludes that the utilization of the moving class learning model effectively contributes to the enhancement of students' speaking skills, particularly when viewed through the lens of motivation.